The Relationship between the Albumin-Bilirubin Ratio and Frailty in Patients with Liver Cirrhosis - Triyanta Yuli Pramana; Alwidya Rosyid Akhmad Permana; Fatichati Budiningsih; Hanung Prasetya (Journal of Public Health Sciences, 2026)
Patients with liver cirrhosis are at risk of impaired liver function, characterized by disturbances in albumin synthesis and bilirubin secretion. The Albumin-Bilirubin (ALBI) score has been reported to be associated with the prognosis of liver cirrhosis patients. This study aimed to analyze the relationship between the ALBI score and frailty in patients with liver cirrhosis. A cross-sectional study was conducted at Dr. Moewardi General Hospital from May to September 2024. A total of 68 patients with liver cirrhosis were included. The dependent variable was frailty, while the independent variable was the ALBI score. Data were collected via a questionnaire and laboratory results, and analyzed using logistic regression. This study found a significant association between a higher ALBI score and frailty in patients with liver cirrhosis. After correcting for data entry errors, the re-analyzed data showed a significant association. A one-unit increase in the ALBI score was associated with a significant increase in the odds of frailty (OR = 13.32; 95% CI = 1.31 to 135.48; p = 0.029). These findings suggest a significant relationship between the ALBI score and frailty in patients with liver cirrhosis, indicating that patients with more severe liver dysfunction (reflected by a higher ALBI score) are more likely to be frail.